The mediation of employee engagement to the relationship of leadership style and corporate performance - Wiguna, Sunanta; Augustine, Yvonne (Technium Social Sciences Journal, 2022)
Objective of research to examine whether leader-member exchange (LMX), Change Oriented Leadership (COL), MBO, Talent Management (TM) have an effect on Corporate Performance (BSC) with Employee Engagement (EME) as a mediating variable. The model used in this research is a stepwise linear regression analysis used to examine about existence of mediating variable between variable in this context. This analysis was carried out in Two-Stage Least Square (2SLS). Research using two proposed models showed similar results that for LMX and TM each had a significant effect on BSC directly or through EME. COL and MBO have an insignificant effect, it is caused by employee disappointment with the company over the leadership style and implementation of MBO. Practitioners, in this case, workers, can continue to improve their performance, because basically, the results achieved are the result of the work hard of each party with a good performance. Engagement between employees and the organization is something that needs to be considered both physically and psychologically. In good conditions, employees will work optimally in carrying out their work with a good performance. In the current pandemic conditions, researchers assume to add measurements by including WFH elements as a new indicator of employee engagement.